Construction Learning Environtment of a Child-Friendly Madrasah Program at Madrasah Aliyah Negeri Salatiga - Zuairiyah; Purnomo (Attractive : Innovative Education Journal, 2025)
This study aims to analyze the construction of a learning environment through the Madrasah Ramah Anah (MRA, Child-Friendly Madrasah) program at Madrasah Aliyah Negeri (MAN, State Islamic Senior Highschool) Salatiga, identify the elements of the learning environment that have been formed, and explain their significance for deep learning and the Kurikulum Berbasis Cinta (KBC, Passionate Based-Curriculum). This study uses a qualitative field approach with a case study design. Data were collected through in-depth interviews, observations, and documentation, then analyzed thematically through coding, category grouping, and theme identification, with data validity ensured through triangulation of sources and techniques. The research results indicate that the learning environment in the MRA program at MAN Salatiga is constructed through an operational institutional foundation, service and mentoring mechanisms, a humanistic culture of interaction, and an active, contextual, and reflective learning design. This construction forms a safe, relational, participatory, and meaningful learning environment, although the experience of safety and the courage to participate are not yet fully equitable among all students. This study found that the MRA program functions not only as an instrument for child protection but also as a socio-pedagogical foundation that enables deep learning and the values of the KBC to be realized in madrasah learning practices.